PERAN LEVERAGE DALAM HUBUNGAN ANTARA INTENSITAS MODAL, INTENSITAS PERSEDIAAN DAN PENGHINDARAN PAJAK - Raainaa, Nural Achmad; Firmansyah, Amrie (Bina Ekonomi, 2025)
Tax revenues represent the primary source of government income in Indonesia, with corporate income tax contributing significantly to the State Budget (APBN). However, the increase in tax realization often does not correspond to the nation’s tax potential, partly due to corporate tax avoidance practices. This study aims to analyze the effect of capital and inventory intensity on tax avoidance, with leverage as a moderating variable, in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2023 period. This sector was selected due to its relatively stable characteristics against changes in economic cycles and its capital-intensive nature in supporting operational activities. This study uses 132 firm-year observations obtained from the companies' annual financial reports. The analysis was conducted using a panel data regression method and a fixed-effects model. The results show that capital intensity positively affects tax avoidance, meaning that the higher the proportion of fixed assets in a company's asset structure, the greater the opportunity for management to engage in tax planning through depreciation policies and operational cost classification. Conversely, inventory intensity does not significantly influence tax avoidance, as inventory value better represents supply chain efficiency and production stability than fiscal strategy. Furthermore, leverage is not proven to moderate the relationship between capital intensity and inventory intensity with tax avoidance, indicating that debt-based funding structures do not influence tax avoidance behavior in stable sector companies such as non-cyclical consumer sectors. These findings strengthen empirical evidence that fixed asset structure is a key determinant of corporate tax planning practices. At the same time, debt use plays a greater role in supporting long-term productive investments. The policy implications of this study emphasize the importance of fiscal oversight of asset-intensive companies by the Directorate General of Taxes (DGT), as well as the need for the Financial Services Authority (OJK) to promote greater transparency in tax policy disclosures in annual reports and corporate sustainability reports.